A survey on readiness of cloud based queuing management system implementation to mobile users - Mohd Saleh, A. H.; Mohamed Radzi, N. A.; Wan Ahmad, W. S. H. M.; C. B. M. Rashidi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Queuing Management System (QMS) has been used in medical facilities to manage crowd systematically and reduce customer dissatisfaction. However, customers that use conventional QMS needs to be within the facility to have access to the QMS information. With the integration of mobile application and cloud based QMS, customers are able to access QMS information anywhere. However, migrating to a new technology requires a study on the readiness of the system. Hence, the objective of this study is to understand the effect of implementing QMS by investigating the effect of time efficiency, cost efficiency, accessibility, reliability, variety, convenience towards customer satisfaction. 311 respondents were given survey questions with 100% response rate. The results were analysed using Statistical Package for the Social Sciences. For reliability analysis, the survey questions were proven to be valid, where factor analysis done supports the results to be effective for further analysis. Correlation and regression analysis done also show that there are influences between the independent variables and the dependent variable.